Metabolic Health Status and the Obesity Paradox in Older Adults. Issue 3 (2nd July 2016) - Cheng, Feon W.; Gao, Xiang; Mitchell, Diane C.; Wood, Craig; Rolston, David D. K.; Still, Christopher D.; Jensen, Gordon L.
ABSTRACT: The explanation for reduced mortality among older persons with overweight or class I obesity compared to those of desirable weight remains unclear. Our objective was to investigate the joint effects of body mass index (BMI) and metabolic health status on all-cause mortality in a cohort of advanced age. Adults aged 74 ± 4.7 (mean ± SD) years at baseline (n = 4551) were categorized according to BMI (18.5–24.9, 25.0–29.9, 30.0–34.9, and ≥35.0 kg/m 2 ) and the presence or absence of a metabolically healthy phenotype (i.e., 0 or 1 risk factors based on a modified Adult Treatment Panel III). Metabolically unhealthy was ≥2 risk factors. There were 2294 deaths over a mean 10.9 years of follow up. Relative to metabolically healthy desirable weight, metabolically healthy overweight or class I obesity was not associated with a greater mortality risk (HR 0.90; 95 CI% 0.73–1.13 and HR 0.58; 95 CI% 0.42–0.80, respectively) (P-interaction <0.001). Results remained consistent in rigorous sensitivity analyses. The "obesity paradox" may be partially explained by the inclusion of metabolically healthy overweight and obese older persons, who do not have elevated mortality risk, in population studies of BMI and mortality.